2014
DOI: 10.1038/nature13045
|View full text |Cite
|
Sign up to set email alerts
|

ZMYND11 links histone H3.3K36me3 to transcription elongation and tumour suppression

Abstract: Recognition of modified histones by “reader” proteins plays a critical role in the regulation of chromatin1. H3K36 trimethylation (H3K36me3) is deposited onto the nucleosomes in the transcribed regions following RNA polymerase II (Pol II) elongation. In yeast, this mark in turn recruits epigenetic regulators to reset the chromatin to a relatively repressive state thus suppressing cryptic transcription2. However, much less is known about the role of H3K36me3 in transcription regulation in mammals. This is furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
337
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(349 citation statements)
references
References 49 publications
11
337
0
1
Order By: Relevance
“…In another study, BS69/ZMYND11 was reported to regulate transcription elongation via its recognition of H3K36me3 on H3.3. Thus it repressed transcriptional programs essential for tumor proliferation (Wen et al, 2014c). The K36M mutation has been found in H3F3B at high prevalence in Chondroblastoma, and was reported to abolish H3K36me3 modification when introduced in 293T cells.…”
Section: H33k36m and Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, BS69/ZMYND11 was reported to regulate transcription elongation via its recognition of H3K36me3 on H3.3. Thus it repressed transcriptional programs essential for tumor proliferation (Wen et al, 2014c). The K36M mutation has been found in H3F3B at high prevalence in Chondroblastoma, and was reported to abolish H3K36me3 modification when introduced in 293T cells.…”
Section: H33k36m and Tumorigenesismentioning
confidence: 99%
“…Several proteins have been reported to read H3K36me3 modifications by virtue of possessing a PWWP domain, including DNMT3a and Brpf1 (Dhayalan et al, 2010;Vezzoli et al, 2010;Wu et al, 2011). A recent report described for the first time, a reader for H3.3-specific K36me3 called BS69/ZMYND11 (Wen et al, 2014c). BS69 has been identified as a tumor suppressor, as it inhibits transcriptional activation regulated by E1A and c-Myb (Hateboer et al, 1995;Ladendorff et al, 2001).…”
Section: H33k36m and Tumorigenesismentioning
confidence: 99%
“…In both studies, the authors used an array of methylated and unmethylated histone peptides and demonstrated that, surprisingly, BS69 preferentially recognizes H3.3K36me3. This highly specific recognition is sensitive to both the methyl level on lysine 36: i.e., BS69 binds to H3.3K36me3, but much less to H3.3K36me0/1/2, as well as the adjacent residues, S31 on H3.3 vs. A31 on H3.1/2 (23,24). Using a cocrystallization approach, the Wen et al study provided at the atomic level mechanistic understanding of how the BS69 reader modalities discriminate H3.3K36me3 from H3.1K36me3.…”
Section: Bs69 Bromo-pwwp Domains Read H33k36me3mentioning
confidence: 99%
“…In these two recent studies (23,24), the BS69 PWWP domain was identified as a specific reader for the K36 trimethylation on histone variant H3.3 (H3.3K36me3) (Fig. 1).…”
Section: Bs69 Bromo-pwwp Domains Read H33k36me3mentioning
confidence: 99%
See 1 more Smart Citation